Estimation of Cinnamoyl Derivatives from Cordia Platythyrsa and Chemiotaxonomical Value of the Cordia Genus - Bernard Dabole; Rostanie Zeukang; Alex de Theodore Atchade; Turibio Tabopda; Benoit Bargui Koubala; Joseph Tanyi Mbafor (Challenges and Advances in Chemical Science Vol. 3, 2021)
The aim of this study was to investigate the roots and the stem barks of Cordia platythyrsa with the view to improve the chemiotaxonomy value in the Cordia genus. Phytochemical investigation of the roots and stem barks of Cordia platythyrsa (Boraginaceae) had led to the isolation of two new cinnamates, the cordicinnamate A compound 1 and the cordicinnamate B compound 2 along with four known compounds. Their structures were established by spectroscopic analysis mainly FAB and TOF –MS, 1H NMR and 13C NMR, COSY, HMBC, HSQC and by comparison with literature data. The cinnamoyl derivatives were reported for the first time in the Cordia genus. The isolation and identification of cinnamoyl derivatives in cordia genus improve the chemiotaxonomy value in this genus.